Giant nanomechanical energy storage capacity in twisted single-walled carbon nanotube ropes - Utsumi, Shigenori; Ujjain, Sanjeev Kumar; Takahashi, Satoshi; Shimodomae, Ryo; Yamaura, Tae; Okuda, Ryosuke; Kobayashi, Ryuichiro; Takahashi, Oga; Miyazono, Satoshi; Kato, Naoki; Aburamoto, Keiichi; Hosoi, Yuta; et al. (Nature, 2024)
A sustainable society requires high-energy storage devices characterized by lightness, compactness, a long life and superior safety, surpassing current battery and supercapacitor technologies. Single-walled carbon nanotubes (SWCNTs), which typically exhibit great toughness, have emerged as promising candidates for innovative energy storage solutions. Here we produced SWCNT ropes wrapped in thermoplastic polyurethane elastomers, and demonstrated experimentally that a twisted rope composed of these SWCNTs possesses the remarkable ability to reversibly store nanomechanical energy. Notably, the gravimetric energy density of these twisted ropes reaches up to 2.1 MJ kg⁻¹, exceeding the energy storage capacity of mechanical steel springs by over four orders of magnitude and surpassing advanced lithium-ion batteries by a factor of three. In contrast to chemical and electrochemical energy carriers, the nanomechanical energy stored in a twisted SWCNT rope is safe even in hostile environments. This energy does not deplete over time and is accessible at temperatures ranging from −60 to +100 °C.
Keywords: Carbon nanotubes and fullerenes; Devices for energy harvesting